Book reviews: George A. Akerlof – An Economic Theorist’s Book of Tales. Essays that Entertain the Consequences of New Assumptions in the Economic Theory - BARNA, Cristina (Annals of Spiru Haret University. Economic Series, 2009)
Book reviews: George A. Akerlof – An Economic Theorist’s Book of Tales. Essays that Entertain the Consequences of New Assumptions in the Economic Theory